Comparative effects of glucagon-like peptide-1 receptor agonists and sodium-glucose co-transporter-2 inhibitors on heart failure with preserved ejection fraction in diabetic patients: a meta-analysis - Arif Albulushi; Desmond Boakye Tanoh; Ahmed Almustafa; Nadya Al Matrooshi; Ronald Zolty; Brian Lowes (Cardiovascular Diabetology, 2024)
Abstract Background Heart failure with preserved ejection fraction (HFpEF) is common in type 2 diabetes mellitus (T2D), leading to high morbidity and mortality. Managing HFpEF in diabetic patients is challenging with limited treatments. Sodium-glucose co-transporter 2 (SGLT2) inhibitors and glucagon-like peptide-1 receptor agonists (GLP1-RA) have shown potential cardiovascular benefits. This meta-analysis compares the effects of GLP1-RA and SGLT2 inhibitors on HFpEF in T2D patients. Methods We conducted a meta-analysis of randomized controlled trials (RCTs) and observational studies evaluating GLP1-RA and SGLT2 inhibitors’ impact on HFpEF in T2D patients. Databases searched included PubMed, MEDLINE, and Cochrane Library up to July 2024. Primary outcomes were changes in left ventricular ejection fraction (LVEF), myocardial fibrosis (extracellular volume fraction, ECV), and functional capacity (6-minute walk test, 6MWT). Secondary outcomes included HbA1c, body weight, and systolic blood pressure (SBP).  Results Twelve studies with 3,428 patients (GLP1-RA: 1,654; SGLT2 inhibitors: 1,774) were included. Both GLP1-RA and SGLT2 inhibitors significantly improved LVEF compared to placebo (GLP1-RA: mean difference [MD] 2.8%, 95% confidence interval [CI] 1.5 to 4.1, p < 0.001; SGLT2 inhibitors: MD 3.2%, 95% CI 2.0 to 4.4, p < 0.001). SGLT2 inhibitors significantly reduced myocardial fibrosis (MD -3.5%, 95% CI -4.2 to -2.8, p < 0.001) more than GLP1-RA (MD -2.3%, 95% CI -3.0 to -1.6, p < 0.001). Functional capacity improved significantly with both treatments (GLP1-RA: MD 45 m, 95% CI 30 to 60, p < 0.001; SGLT2 inhibitors: MD 50 m, 95% CI 35 to 65, p < 0.001). Secondary outcomes showed reductions in HbA1c (GLP1-RA: MD -1.1%, 95% CI -1.4 to -0.8, p < 0.001; SGLT2 inhibitors: MD -1.0%, 95% CI -1.3 to -0.7, p < 0.001) and body weight (GLP1-RA: MD -2.5 kg, 95% CI -3.1 to -1.9, p < 0.001; SGLT2 inhibitors: MD -2.0 kg, 95% CI -2.6 to -1.4, p < 0.001). Both treatments significantly lowered SBP (GLP1-RA: MD -5.2 mmHg, 95% CI -6.5 to -3.9, p < 0.001; SGLT2 inhibitors: MD -4.8 mmHg, 95% CI -6.0 to -3.6, p < 0.001). Conclusions GLP1-RA and SGLT2 inhibitors significantly benefit HFpEF management in T2D patients. SGLT2 inhibitors reduce myocardial fibrosis more effectively, while both improve LVEF, functional capacity, and metabolic parameters. These therapies should be integral to HFpEF management in diabetic patients. Further research is needed on long-term outcomes and potential combined therapy effects.